A novel enrichment and sensitive method for simultaneous determination of 15 phthalate esters in milk powder samples. (January 2022) - Ma, Jin-Kui; Wei, Shou-Lian; Tang, Qing; Huang, Xiao-Chen
Abstract: Phthalate acid esters (PAEs) with superior performance are widely used. However, the long-term intake of PAEs seriously damages the human body. In this work, a novel type of magnetic molecularly imprinted polymer (mMIP) was synthesized and coupled with gas chromatography–mass spectrometry (GC/MS) for the selective separation and determination of 15 PAEs in milk powder samples. Key mMIP variables, i.e. (1) NaCl dosage, (2) eluent type and amount, (3) extraction and elution time), and (4) reusability, were investigated to determine the optimal magnetic solid phase extraction conditions. Results revealed that the mMIPs had good recognition specificity for the template molecules. Under the optimized conditions, 15 PAEs were successfully separated and analyzed by GC/MS. Results showed a good linearity in the range of 0.05–10.0 μg/mL for different PAEs' concentration. The detection limit was 0.2–0.8 μg/kg, the average recovery was 83.0%–104%, and the relative standard deviation was 2.4 %–8.6% ( n  = 5). This new sample and rapid pretreatment method was successfully applied to the monitoring of trace plasticizing agent residues in milk powder. Highlights: A novel mMIP was synthesized by using PAEs as template molecules. The prepared MIP has been characterized and can specifically recognize PAEs. The main influencing parameters in the sample preparation process were investigated. The established method could be applied to detect PAE residues in milk powder.